About one Problematic Moment in Textbooks on Probability Theory - Zhubanysheva А.Ж.; Taugynbaeva Г.Е.; Nauryzbayev Н.Ж.; Temirgaliyev Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2022)
In the article is studied, according to our opinion, the problematic moment "An experiment was performed, the outcome is known. Did the event occur?" and the associated calculations of the frequencies of the occurrence of this event in the context of determining the probability. Namely, theoretical and practical detailed discussions of these topics are justificated.